Fission yeast RNA‐binding proteins Puf2 and Puf4 are involved in repression of ferrireductase Frp1 expression in response to iron. Issue 5 (21st October 2021) - Beaudoin, Jude; Normant, Vincent; Brault, Ariane; Henry, Darren J.; Bachand, François; Massé, Éric; Chua, Gordon; Labbé, Simon
Abstract: This study identifies a post‐transcriptional mechanism of iron uptake regulation by Puf2 and Puf4 of the Pumilio and FBF (Puf) family of RNA‐binding proteins in Schizosaccharomyces pombe . Cells expressing Puf2 and Puf4 stimulate decay of the frp1 + mRNA encoding a key enzyme of the reductive iron uptake pathway. Results consistently showed that frp1 + mRNA is stabilized in puf2Δ puf4Δ mutant cells under iron‐replete conditions. As a result, puf2Δ puf4Δ cells exhibit an increased sensitivity to iron accompanied by enhanced ferrireductase activity. A pool of GFP‐ frp1 + 3′UTR RNAs was generated using a reporter gene containing the 3′ untranslated region (UTR) of frp1 + that was under the control of a regulatable promoter. Results showed that Puf2 and Puf4 accelerate the destabilization of mRNAs containing the frp1 + 3′UTR which harbors two Pumilio response elements (PREs). Binding studies revealed that the PUM‐homology RNA‐binding domain of Puf2 and Puf4 expressed in Escherichia coli specifically interacts with PREs in the frp1 + 3′UTR. Using RNA immunoprecipitation in combination with reverse transcription qPCR assays, results showed that Puf2 and Puf4 interact preferentially with frp1 + mRNA under basal and iron‐replete conditions, thereby contributing to inhibit Frp1 production and protecting cells against toxic levels of iron. Abstract : Under iron‐replete conditions, it is known that the transcription factor Fep1 represses expression of the frp1 + gene (mechanism #1) in fission yeast. This work identifies a novel posttranscriptional mechanism (#2) that consists of frp1 + mRNA destabilization by Puf2 and Puf4 through Pumilio response elements (PREs) in the frp1 + 3′ untranslated region. The Puf2/Puf4‐mediated decay of frp1 + mRNA ensures rapid inhibition of the reductive iron uptake, thereby protecting cells against excessive accumulation of iron.